2022
DOI: 10.3389/fimmu.2022.858069
|View full text |Cite
|
Sign up to set email alerts
|

ROCK inhibition with Y-27632 reduces joint inflammation and damage in serum-induced arthritis model and decreases in vitro osteoclastogenesis in patients with early arthritis

Abstract: Rheumatoid arthritis (RA) is a common chronic inflammatory disease affecting primarily peripheral joints, which is only partially controlled with current treatments. RA leads to pain, disability, deformities, and life expectancy shortening. Its pathogenesis is complex involving multiple cell types and signaling pathways that we incompletely understand. One of the pathways we have elucidated starts with WNT5A signaling and contributes to the aggressive phenotype of the RA synoviocytes through RYK-RhoA/ROCK sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 73 publications
1
4
0
Order By: Relevance
“…remains unclear. Previous studies have indicated that ROCK inhibitors restrained osteoclast differentiation(Rodríguez-Trillo et al, 2022), and our current work supported this finding, as we observed that Y-27632 reduced osteoclast formation (Figure6k). Furthermore, we found that Y-27632 decreased the expression of NFATc1 and disrupted actin formation, which further supported the notion that ROCK inhibition played a role in osteoclastogenesis (Figures6l and 8b).To better illustrate the effect of Phi on the RhoA/ROCK1 pathway, we examined the protein levels of ROCK1 and downstream signaling.…”
supporting
confidence: 90%
“…remains unclear. Previous studies have indicated that ROCK inhibitors restrained osteoclast differentiation(Rodríguez-Trillo et al, 2022), and our current work supported this finding, as we observed that Y-27632 reduced osteoclast formation (Figure6k). Furthermore, we found that Y-27632 decreased the expression of NFATc1 and disrupted actin formation, which further supported the notion that ROCK inhibition played a role in osteoclastogenesis (Figures6l and 8b).To better illustrate the effect of Phi on the RhoA/ROCK1 pathway, we examined the protein levels of ROCK1 and downstream signaling.…”
supporting
confidence: 90%
“…[ 40 ] Inhibiting RhoA/ROCK can alleviate OA in vitro and in vivo. [ 41 ] Therefore, we assessed the role of RhoA/ROCK in CTF degradation in patients with OA. We inhibited RhoA/ROCK using Y‐27632 and found that F‐actin and FA expression decreased, F‐actin was distributed (Figure 4a), and the CTF significantly recovered (Figure 4e).…”
Section: Resultsmentioning
confidence: 99%
“… 406 As Wnt5a promotes RA via ROCK signaling, ROCK inhibitor Y-27632 inhibits Wnt5a-induced RA FLS migration and reduced inflammatory cytokines IL-1β, IL-6, MMP3, MMP9 and MMP13 levels. 408 Moreover, traditional Chinese medicine, such as Ginkgolide B and Resveratrol, show anti-RA effect for reducing articular cartilage and bone destruction and decreasing inflammatory cytokine levels through suppressing Wnt5a level. 409 , 410 All these results suggest Wnt5a a critical drug target for treating RA (for review, see Huang et al 381 ).…”
Section: Targeting Wnt Signaling In Bone Disease Treatmentmentioning
confidence: 99%